Edukacja wczesnoszkolna w splocie sprzeczności = Early school education in a tangle of contradictions - Kopaczyńska, Iwona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author discusses the contradictions regarding three issues related to early school education. They can be observed in the following range: the socially shared views on the education of children in the early school stage;the way the teachers understand their own teaching activity; the strategy of didactic thinking present in the early school education. Each one of these issues is a specific perspective on the educational observation of the youngest pupils and it significantly impacts the organization, possible changes and the process in its field.
Keywords: poglądy na temat edukacji; rozumienie własnej edukacji; rozumienie nauczycielskiej roli; strategie dydaktyczne; edukacja wczesnoszkolna; early childhood education; views on education; understandingone`s own education; understanding the teacher`s role; didactic strategies